Kualitas Fisik dan Mikrobiologis Bakso Daging Sapi Pada Penyimpanan Suhu yang Berbeda - Ismail, M.; Kautsar, R.; Sembada, P.; Aslimah, S.; Arief, I. I. (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2016)
This study was conducted to determine the effect of different temperatures storage on the value of pH, water holding capacity, water activities, Total Plate Count and Escherichia coli contamination of beef meatballs during storage. The result showed that the highest pH value was in the freezer storage (5.83 ± 0.023). The highest value of water holding capacity was obtained at treatment dingingerator storage (23.33 ± 7.026 % water-free), while the results of the analysis of variance showed that effect of different temperature storage was not signiicant (P <0.05) to the water holding capacity. Aw values in this study ranged from 0.854 to 0.908. Aw values at refrigerator and freezer storage were signiicantly higher (P> 0.05) than the meatballs in fresh condition. The analysis of variance showed that treatment of different temperature storage had no signiicant effect (P <0.05) for Total Plate Count (TPC). Mean of TPC (log10 cfu/g) ranged between 5,30 + 0,62 to 5,86 + 0,65. E. coli contamination was found in meatballs stored at freezer storage. Treatment of different temperature storage was signiicantly affect water activity and was not effect on pH, water holding capacity and microbiological content (TPC and E. Coli).